PEMBERDAYAAN KELOMPOK WANITA TANI MELALUI INOVASI OLAHAN PRODUK UNGGULAN LOKAL DESA SALAMREJO KABUPATEN KULON PROGO - Nanik Dara Senjawati; Heti Herastuti; Liana Fatma Leslie Pratiwi (Dharma: Jurnal Pengabdian Masyarakat, 2022)
One of the ways to empower rural communities is to empower women farmer groups. One of the program activities in the women farmer group is the processing of agricultural commodities. The activity of processing agricultural commodities into a food product (off farm) can provide added value to the product and can make the product to be superior product. Limited knowledge related to product processing is a problem that can be overcome through community empowerment programs. The purpose of this activity is that women farmer groups in every hamlet in Salamrejo Village, Kulon Progo Regency can utilize superior commodities in their area into processed food products that have added value. The method used in this activity is counseling (edu-agriculture) and direct training practices on the manufacture of processed foods made from corn. The results of the activities obtained are in the form of increasing the knowledge of members of the women's farmer group regarding how to process food made from corn commodities so that they are cost-efficient and have a high selling price and can practice food processing made from corn commodities independently in groups.